Identification of the Staphylococcus aureus endothelial cell surface interactome by proximity labeling - Marcel Rühling; Fabio Schmelz; Alicia Kempf; Kerstin Paprotka; Martin J. Fraunholz (mBio)
ABSTRACT Virulence strategies of pathogens depend on interaction with host cells. The binding and activation of receptors located on the plasma membrane are crucial for the attachment to or pathogen internalization by host cells. Identifying host cell receptors is often difficult, and hence, the identity of many proteins that play important roles during host-pathogen interaction remains elusive. We developed a novel proximity labeling approach by decorating the opportunistic pathogen Staphylococcus aureus with ascorbate peroxidase 2. Upon addition of hydrogen peroxide, the peroxidase initiates proximity biotinylation of S. aureus host interaction partners, thereby enabling the identification of these proteins. Here, we demonstrate an endothelial cell surface interactome of 305 proteins, including novel S. aureus co-receptors such as neuronal adhesion molecule, protein tyrosine kinase PTK7, melanotransferrin, protein-tyrosine kinase MET, and CD109. Filtering the interactome for validated surface proteins resulted in a list of 89 protein candidates, 53% of which were described to interact with S. aureus or other pathogens.IMPORTANCEStaphylococcus aureus is an opportunistic pathogen that enters host cells such as epithelial or endothelial cells. Intracellular pathogens have been observed in vivo and are thought to serve immune evasion, avoidance of antibiotic treatment, and chronicity of infection. Thus, it is important to understand the mechanisms by which the bacteria are internalized by host cells; however, screening for pathogen-host receptors is difficult. Here, we developed a novel proximity labeling approach, which enabled the identification of several previously unknown host receptors of S. aureus that are engaged during a rapid uptake pathway for the bacteria.